Modeling human prostate cancer progression in vitro. (22nd December 2018) - Liu, Teresa T; Ewald, Jonathan A; Ricke, Emily A; Bell, Robert; Collins, Colin; Ricke, William A
Abstract: Detailed mechanisms involved in prostate cancer (CaP) development and progression are not well understood. Current experimental models used to study CaP are not well suited to address this issue. Previously, we have described the hormonal progression of non-tumorigenic human prostate epithelial cells (BPH1) into malignant cells via tissue recombination. Here, we describe a method to derive human cell lines from distinct stages of CaP that parallel cellular, genetic and epigenetic changes found in patients with cancers. This BPH1-derived Cancer Progression (BCaP) model represents different stages of cancer. Using diverse analytical strategies, we show that the BCaP model reproduces molecular characteristics of CaP in human patients. Furthermore, we demonstrate that BCaP cells have altered gene expression of shared pathways with human and transgenic mouse CaP data, as well as, increasing genomic instability with TMPRSS2–ERG fusion in advanced tumor cells. Together, these cell lines represent a unique model of human CaP progression providing a novel tool that will allow the discovery and experimental validation of mechanisms regulating human CaP development and progression. This BPH1-derived Cancer Progression (BCaP) model represents different stages of cancer. The BCaP model reproduces molecular characteristics of prostate cancer. The cells have altered gene expression with TMPRSS2-ERG fusion representing a unique model for prostate cancer progression.